Assessment of users’ preferences for sawn wood species in Ibadan metropolis, Nigeria (2016)
Users of wood still have preferences despite increasing reduction in the availability of wood species. This study was therefore carried out to assess the users’ preferences for sawn wood species in Ibadan metropolis, Nigeria. A cross-sectional survey study, which employed questionnaire and on-site observations, was used. A sample of 210 respondents was purposively selected from twenty one associations’ of sawn wood users comprising mixtures of active furniture makers and carpenters in five local government areas of Ibadan metropolis. Data were analysed using descriptive statistics such as percentages, frequency and ranking. Of the 27 species, users expressed the highest preference for Gmelina arborea, which ranked 1st with a frequency of 99.5%, and least preferred was Funtumia elastica with a frequency of 2.4%. Sawn wood users comprise furniture makers only (29.5%), carpenters only (2.9%), and combined furniture makers/carpenters (67.6%). Based on the wood conversion methods, 73.3% of users preferred wood from band-saw milling and chain-saw milling, 26.7% preferred wood from band- saw milling only, while none preferred wood from chain-saw milling only. Criteria for users’ preferences for sawn wood species were durability (50%), workability (28.5%), and attractive colour of the species (22.5%). In addition, users expressed accuracy in dimension (62.9%), ease to work on (27.1%), and specification order by the final consumers (10%) as criteria for preferring sawn wood from band-saw milling to that from chain-saw milling. Efforts should be made to shift the consumption paradigm from reliance on natural forests to conservation approaches focusing on market oriented mass establishment of plantations of the preferred species.